The European model of service delivery: a partnership approach in Northern Ireland - Knox, Colin (1998)
The volatile political and security environment of Northern Ireland has for 26 years focused attention on tackling the, so far, intractabale constitutional question of its position within the United Kingdom and the island of Ireland. The collapse of the IRA ceasefire in February 1996 and fears of a possible return to violence by Protestant paramilitaries have heightened tensions. This protracted period of violence has deflected attention away from a system of public service administration in Northern Ireland characterized by serious problems of accountability. Essential public services operate under the aegis of appointed boards, and the major repository of power, under a system of Direct Rule from Westminster, is the Secretary of State for Northern Ireland, a British Cabinet Minister. Under a recent European initiative (the EC Peace and Reconciliation Programme, 1995) an alternative model of service delivery provides a major opportunity for administrative reform in Northern Ireland. This model is based on a partnership approach in which councillors, the private and voluntary sectors collaborate to deliver services. Although still in its early stages, this approach could sever the link between political progress and administrative change which has contributed for too long to the `democratic deficit' in Northern Ireland. - Reproduced
Keywords: Public administration - Ireland, Northern; Public administration